The hidden histories of war crimes trials - Heller, Kevin Jon; Simpson, Gerry J. (Oxford : Oxford University Press, 2014)
Several war crimes trials are well-known to scholars, but others have received far less attention. This book assesses a number of these little-studied trials to recognise institutional innovations, clarify doctrinal debates, and identify their general relevance to the development of international criminal law.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 13, 2013).
Keywords: War crime trials